The cosmic timeline implied by the highest redshift quasars - Fulvio Melia (European Physical Journal C: Particles and Fields)
Abstract The conventional picture of supermassive black-hole growth in the standard model had already been seriously challenged by the emergence of $$\sim 10^9\;M_\odot $$ ∼ 10 9 M ⊙ quasars at $$z\sim 7.5$$ z ∼ 7.5 , conflicting with the predicted formation of structure in the early $$\varLambda $$ Λ CDM Universe. But the most recent JWST discovery of a $$\sim 10^8\;M_\odot $$ ∼ 10 8 M ⊙ source at $$z\sim 10.1$$ z ∼ 10.1 argues even more strongly against the possibility that these black holes were created in Pop II or III supernovae, followed by Eddington-limited accretion. Attempts at resolving this anomaly have largely focused on the formation of seeds via an exotic, direct collapse of primordial gas to an initial mass $$\sim 10^5\;M_\odot $$ ∼ 10 5 M ⊙ – a process that has never been seen anywhere in the cosmos. Our goal in this Letter is to demonstrate that the emergence of these black holes is instead fully consistent with standard astrophysics in the context of the alternative Friedmann–Lemaître–Robertson–Walker cosmology known as the $$R_h=ct$$ R h = c t universe. We show that, while the predicted evolution in the standard model is overly compressed, the creation, growth and appearance of such high-z quasars fall comfortably within the evolutionary history in this cosmology, thereby adding considerable observational support to the existing body of evidence favoring it over the standard scenario.